Association of expression of selenoprotein P in mRNA and protein levels with metabolic syndrome in subjects with cardiovascular disease: Results of the Selenegene study. (March 2017) - Gharipour, Mojgan; Sadeghi, Masoumeh; Salehi, Mansour; Behmanesh, Mehrdad; Khosravi, Elham; Dianatkhah, Minoo; Haghjoo Javanmard, Shaghayegh; Razavi, Rouzbeh; Gharipour, Amin
Abstract: Background: Selenoprotein P (SeP) is involved in transporting selenium from the liver to target tissues. Because SeP confers protection against disease by reducing chronic oxidative stress, the present study aimed to assess the level of SeP in the serum of patients with metabolic syndrome (MetS) with a history of cardiovascular disease (CVD). Methods: A cross‐sectional study was conducted in 63 and 71 subjects with and without MetS in the presence of documented CVD. All demographic, anthropometric and cardiometabolic variables (lipids, blood glucose, blood pressure) were assessed. Lifestyle‐related factors and personal history and familial CVD risk factors were recorded. The expression of SELP in mRNA and protein levels in the serum was measured, and MetS was determined using ATPIII criteria. Binary logistic regression analysis demonstrated MetS and SeP to be dependent and independent variables, respectively. Results: Mean of systolic and diastolic blood pressure, triglyceride, high‐density lipoprotein‐cholesterol, fasting blood sugar, body mass index and waist circumference were higher among subjects with MetS ( p = 0.05). The mean of selenium was higher among subjects with MetS, whereas the mean of SeP was lower among subjects with MetS ( p < 0.001). In the unadjusted model, the SeP had decreased odds for MetS [odds ratio (OR) = 0.995; 95% confidence interval (CI) = 0.989–1.00] ( p < 0.04). Furthermore, the association between MetS and SeP levels remained marginally significant even after adjusting for potential confounders such as age, gender, family history, smoking status and nutrition. SeP and waist circumference show a significant relationship (OR =0.995; 95% CI = 0.990–1.00) ( p < 0.033). Conclusions: We have demonstrated a significant decrease in circulating SeP levels according to MetS status in patients with documented cardiovascular disease.